The relationship of limb muscle power, balance, and coordination with instep shooting ability: A correlation study in under-18 football athletes - Burhaein, E.; Ibrahim, B. K.; Pavlovic, R. (International Journal of Human Movement and Sports Sciences, 2020)
The purpose of this study was to examine the relationship between leg muscle power, balance, coordination, and shooting skills in soccer. Participants in this study used 89 soccer athletes with an age range of 15-18 years (M = 17.6; SD: 1.30). The research instrument used a coordination test (soccer wall volley test), balance test (modified bass test), leg muscle power (standing long jump test or broad jump), and shooting skills test. Data collection techniques, namely by measuring tests and measurements by the implementation procedure. Data analysis in this study was using Pearson correlation and regression analysis with the help of the IBM SPSS 24 application. The results showed that: 1) There was a relationship between leg muscle power and shooting ability using instep; 2) There is a relationship between balance and the ability to shoot using the instep; 3) There is a coordination relationship with the ability to shoot using the instep; and 4) There is a relationship between leg muscle power, balance, and coordination with the shooting ability using the instep. Recommendations for further research are suggested to involve other independent variables (X) that are relevant to this study, such as leg length, running speed, and angle of impact.